2016
DOI: 10.1002/ece3.2231
|View full text |Cite
|
Sign up to set email alerts
|

Thermal reaction norms can surmount evolutionary constraints: comparative evidence across leaf beetle species

Abstract: One of the leitmotifs of the ecophysiological research on ectotherms is the variation and evolution of thermal reaction norms for biological rates. This long‐standing issue is crucial both for our understanding of life‐history diversification and for predicting the phenology of economically important species. A number of properties of the organism's thermal phenotype have been identified as potential constraints on the evolution of the rate–temperature relationship. This comparative study addresses several suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…While recent studies showed that T opt and CT max increase after evolving at higher temperatures (Listmann et al, 2016), we do not know how the whole thermal reaction norm may evolve in phytoplankton; for example, adaptation to high temperatures may lead to a decrease in fitness at low temperatures, as previously observed in bacteria (Bennett & Lenski, 1993) and bacteriophages (Knies, Izem, Supler, Kingsolver, & Burch, 2006). Selection may change the slope and curvature (first and second derivatives) of the thermal reaction norm as well (Kutcherov, 2016), especially if some cardinal temperatures are more evolutionarily labile than others (Araújo et al, 2013).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…While recent studies showed that T opt and CT max increase after evolving at higher temperatures (Listmann et al, 2016), we do not know how the whole thermal reaction norm may evolve in phytoplankton; for example, adaptation to high temperatures may lead to a decrease in fitness at low temperatures, as previously observed in bacteria (Bennett & Lenski, 1993) and bacteriophages (Knies, Izem, Supler, Kingsolver, & Burch, 2006). Selection may change the slope and curvature (first and second derivatives) of the thermal reaction norm as well (Kutcherov, 2016), especially if some cardinal temperatures are more evolutionarily labile than others (Araújo et al, 2013).…”
Section: Introductionmentioning
confidence: 83%
“…While recent studies showed that T opt and CT max increase after evolving at higher temperatures (Listmann et al., ), we do not know how the whole thermal reaction norm may evolve in phytoplankton; for example, adaptation to high temperatures may lead to a decrease in fitness at low temperatures, as previously observed in bacteria (Bennett & Lenski, ) and bacteriophages (Knies, Izem, Supler, Kingsolver, & Burch, ). Selection may change the slope and curvature (first and second derivatives) of the thermal reaction norm as well (Kutcherov, ), especially if some cardinal temperatures are more evolutionarily labile than others (Araújo et al., ). For example, by comparing the peak sharpness at T opt and the width (°C) of the upper tail of the thermal reaction norm in cold‐ versus warm‐selected populations, we may make inferences regarding the evolutionary lability of the maximum growth rate at T opt ( μ opt ), and of T opt itself, relative to that of CT max ; the upward concavity below T opt and the location of the inflection point on the thermal reaction norm contribute greatly to the magnitude of trade‐offs between growth at temperatures below T opt versus above, which can be indicative of generalist‐specialist and/or resource allocation trade‐offs (Angilletta et al., ; Gilchrist, ).…”
Section: Introductionmentioning
confidence: 99%
“…nebulosa and G . graminea strongly depart from a linear relationship with temperature, which is not expected to occur in the non-stressful thermal range 16 . Data for C .…”
Section: Developmental Responses To Temperature In Tortoise Beetlesmentioning
confidence: 90%
“…The HiB hypothesis is also implicit in the universal temperature dependence concept of the Metabolic Theory of Ecology (MTE) 5,6,25 . However, whether the HiB hypothesis holds across organisms and environments is a question that is still debated 24,26,27 . Deviations from a HiB pattern would indicate that thermodynamic constraints are compensated for by other mechanisms.…”
Section: Introductionmentioning
confidence: 99%